PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT ADAKOM INTERNATIONAL TECHNOLOGY JAKARTA UTARA - Astuti, Fitria; Sri Rahayu, Rian (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of transformational leadership and organizational culture on employee performance both partially and simultaneously at PT Adakom International Technology. This research method uses a quantitative descriptive method with a survey approach. The sampling technique used in this research is based on the saturated sampling method, where 48 samples from 78 members of the population were taken using a saturated sampling technique. Data analysis and testing techniques include validity and reliability tests, classical assumption tests, statistical tests including multiple linear regression tests, coefficient of determination tests, and hypothesis tests. In the first hypothesis test, namely the influence of transformational leadership (X1) on employee performance at PT Adakom International Technology, it was obtained that t count > t table or (6.913 > 1.679). This was also strengthened by the ρ value < Sig. 0.050 or (0.000 < 0, 05). So it can be stated partially to show that there is a significant influence on employee performance (Y) at PT Adakom International Technology. Meanwhile, testing the second hypothesis, namely the influence of organizational culture (X2) on employee performance (Y) at PT Adakom International Technology, obtained the calculated t value < ttable or (-0.032 < 1.679). This was also strengthened by the ρ value > Sig.0.050 or ( 0.975 > 0.05). So it can be stated partially to show that there is no significant influence on employee performance (Y) at PT Adakom International Technology. The third hypothesis test, namely the influence of transformational leadership (X1) and organizational culture (X2) on employee performance (Y) at PT Adakom International Technology, obtained a value of Fcount > Ftable or (23.897 > 3.204). This is also reinforced by the ρ value < Sig.0 .05 or (0.000 < 0.05). This means that simultaneously transformational leadership and organizational culture have a significant effect on employee performance (Y) at PT Adakom International Technology.